Validation of bridge health monitoring system using temperature as a proxy for damage. Issue 9 (29th June 2020) - OBrien, Eugene J.; Heitner, Barbara; Žnidarič, Aleš; Schoefs, Franck; Causse, Guillaume; Yalamas, Thierry
Summary: In this paper, damage indicators are presented for bridges based on measured data collected under uncontrolled traffic conditions. The test bridge considered is a small stiff concrete culvert with low dynamics, making it suboptimal for monitoring with accelerometers. Largely static strain responses are measured, with the variability in the vehicle weights and configurations addressed by handling the data in statistical terms. Continuously recorded temperature data are used in an alternative and innovative way to validate damage indicators. Temperature change causes stiffness change in concrete structures. It is posited that temperature can be used as a proxy for bridge damage as, while the effects are clearly different, both cause changes in flexural rigidity and therefore in bridge response to load. It is demonstrated here, using field data, that the damage indicators are sensitive to temperature change. Strain and temperature data for a 2‐year period are obtained for a culvert bridge in Slovenia. The defined damage indicators are calculated for the strain data and validated using the simultaneously recorded temperature data. Two ways of using the proposed damage indicators together with the information about temperature for bridge structural health monitoring (SHM) are also presented: one is including the mean and standard deviation of the damage indicators and a compensation for the temperature effect and another to obtain directly the modified Z score, which is used for identifying outliers, and draw a 2D risk map having damage indicator and temperature on the two axes.